Absenteísmo dos usuários aos serviços de saúde no município de Vila Velha no Estado do Espírito Santo - Tristão, Flavio Ignes (2016)
The access to health services is a major challenge for the care guarantee based on the principles of universality, comprehensiveness and equity. As a central component to achieve this purpose, the Primary Care is recognized as the main access to the realization of care and organizes the Health Care Networks, implicated in comprehensiveness of health actions at different levels of complexity. Parallel to this, is the paradox of evident occurrence of non-access, ie, absenteeism users to health services. This study aimed to analyze the access, use and absenteeism users to health services in the municipal health network from Vila Velha - ES. The specific objectives included: analyzing the amount of scheduled clinic visits and the occurrence of absenteeism in the Basic Attention municipality in the years 2014 and 2015; analyze the amount of scheduled clinic visits and the occurrence of absenteeism in the Specialized Care of Vila Velha in 2015; analyze the queries marking process in the two levels of care and; analyze the causal factors related to absenteeism users to health services mentioned by health professionals and by the users. For this we used quantitative methodologies (descriptive statistical analysis of secondary data) and qualitative (thematic analysis of interviews), which was supplemented to provide a thorough understanding of the studied aspects. The results indicated that users' access to services of Primary Care and Specialized is performed not focused manner on the user, and that absenteeism is related to employee care model and way of organizing access two levels of attention, and consider related factors ace dimensions of access and availability of services, the payment power, the degree of information and acceptability. The study pointed out the importance of valuing the subjective aspects of the relationship between professionals and users, which can directly affect the quality of the understanding of the health conditions of users and also to build mutual respect of bonds and trust between those involved in the production process for care.